Secondary students' understanding of the gene concept : an analysis of conceptual change from multiple perspectives. - Venville, Grady J. (Curtin University, 1997)
A journey into the past century of genetics history reveals transformations of the concept of the gene through notions of discrete units that obeyed Mendelian laws to the modem bewildering gene concept. We can no longer say that a gene is a sequence of DNA that continuously and uniquely codes for a particular protein - it is the phenotype that defines the gene, rather than the other way around. Research into learning in genetics has largely focussed on issues such as problem solving and the process of meiosis. The central concept of the gene, however, has had little attention. How do students learn about the concept of the gene during an introductory high school genetics course? Is it possible to justify an analogy between the historical development of the concept of the gene and student learning? Can student learning about the gene be described as conceptual change and what are the factors that might influence this process? These are the issues that are addressed in this thesis.The general purpose of this study was to investigate Year 10 students' learning about the concept of the gene. The theoretical framework is embedded in the personal and social paradigms of constructivism and a multidimensional interpretive framework for conceptual change was utilised, enabling the data to be interpreted from ontological, epistemological and social/affective perspectives.A total of eight classroom sites were used to collect data as a series of linked case studies. Data from three of these cases were used to investigate Year 10 student learning about the concept of the gene and one of the cases was used to make an in-depth examination of individual student learning and conceptual change. The larger series of eight cases was drawn upon to provide data to support assertions made about the factors influencing conceptual change. Methods of data collection included classroom observations, student interviews, teacher interviews, student work-sheets and classroom quizzes. Traditional notions of research rigour were side-stepped for different standards that better suit the paradigm of naturalistic or constructivist inquiry. Credibility, transferability, dependability and confirmability were enhanced by a thorough system of triangulation at the data source and collection level and at the data interpretation level for each of the research questions. Theory triangulation also was utilised through the multidimensional framework for conceptual change. In addition, methodology and case studies with a thick description that allow the readers to proceed on their own tracking and interpretation process are provided.The results of the research reported in this thesis are examined from several different perspectives. From an ontological perspective, Year 10 student learning about the concept of the gene is described by a proposed learning pathway that consists of four ontologically distinct models. The majority of the students in the classes, however, did not progress the entire length of the pathway, rather they completed their introductory genetics course with an "active particle gene" conception. This is the second model in the pathway. In other words, few students were found to have a modern conception of the gene.From an epistemological perspective of conceptual change, six students' post instruction conceptions of genes were classified as being intelligible, plausible or fruitful to the learner. For example, at the end of the genetics course, Alastair had an active particle gene" conception that he viewed as intelligible and plausible and Douglas had a "productive sequence of instructions gene" conception that was intelligible, plausible and fruitful. The student learning investigated in this study was described as conceptual change of the weaker kind that proceeded in an evolutionary manner because the new conceptions involved detailed explanations of the gene concept and were reconciled with old conceptions.A social/affective perspective revealed information about how the teaching approach and student interest in genetics influenced the process of conceptual change. Lack of student interest in submicroscopic explanatory phenomena and algorithmic approaches to problem solving were found to inhibit learning about the gene concept. The nature of the content was another perspective used to examine conceptual change. The process aspects of genetics content were said by teachers to be difficult to teach, and students found it difficult to link together ideas taught in genetics such as the double helix structure of DNA, the genetic code, protein synthesis and phenotypic expression. The different levels of representation in genetics content confused students; for example, Anna was unable to differentiate between submicroscopic DNA structure and symbolic representations of the genetic code such as the letters A, T, C and G.Implications from the study are that for students to construct a better understanding of the concept of the gene, teachers and curriculum writers should use the gene as a central organising concept in genetics courses and explicitly encourage students to build links with other genetics concepts. Improvements need to be made in the way that teachers teach genetics processes so that students are actively involved in thinking about the processes, especially by making the connections between the structure and function of genes. In addition, students need to be involved in learning strategies that will help to raise the status of sophisticated models of genes in their cognitive structures.Having the multidimensional framework for conceptual change as the interpretive framework and utilising different perspectives of conceptual change enabled triangulation of the theoretical interpretations of the data. This can be likened to creating a three dimensional picture of a learning situation rather than the equivalent of a linear, or two dimensional representation of a complex three dimensional phenomenon. A major implication for conceptual change research from this study is that the multidimensional framework has the potential to enable researchers and teachers to better understand the process of conceptual change in many fields. The thesis concludes with a discussion of the limitations of the study and future directions for research.